2019
DOI: 10.1021/acs.iecr.9b00251
|View full text |Cite
|
Sign up to set email alerts
|

Recyclability of Encapsulated Ionic Liquids for Post-Combustion CO2 Capture

Abstract: Ionic liquids (ILs) with aprotic heterocyclic anions (AHAs) are promising candidates for post-combustion carbon capture technologies since they react with CO2 stoichiometrically and reversibly. CO2 solubilities in two AHA-ILs, triethyl­(octyl)­phosphonium 2-cyanopyrrolide ([P2228]­[2CNPyr]) and triethyl­(octyl)­phosphonium benzimidazolide ([P2228]­[BnIm]), are reported for multiple temperatures and a third, triethyl­(octyl)­phosphonium 6-bromobenzimidazolide ([P2228]­[6-BrBnIm]), at one temperature. Ionic liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 43 publications
1
49
0
Order By: Relevance
“…The only exception was [P 4,4,4,4 ][Ac] that is solid at temperatures below 333 K. The encapsulation of IL not only enhances the mass transport properties but also lets us use ILs that would not reach the thermodynamic equilibrium under reasonable conditions due to the kinetic limitations . This improvement is due to the large increase of the contact surface area between the gas phase and the amino acid IL, upon dispersion of the absorbent in submicrodrops, in good agreement with previous results , , , ,…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The only exception was [P 4,4,4,4 ][Ac] that is solid at temperatures below 333 K. The encapsulation of IL not only enhances the mass transport properties but also lets us use ILs that would not reach the thermodynamic equilibrium under reasonable conditions due to the kinetic limitations . This improvement is due to the large increase of the contact surface area between the gas phase and the amino acid IL, upon dispersion of the absorbent in submicrodrops, in good agreement with previous results , , , ,…”
Section: Resultssupporting
confidence: 87%
“…Nonetheless, many have pursued different approaches aiming at minimizing these limitations, while maintaining the enhanced gas sorption capacity, such as using a solid phase to immobilize the solvents and the use of gas‐liquid membrane contactors for gas absorption processes , . Recently, the confinement of solvents in nano‐porous matrices has been proposed as a promising technique for gas separation, with improved mechanical integrity capable of overcoming the major drawbacks of the bulk solvents, such as high viscosity and slow gas diffusivity, and ultimately, requiring reduced quantities of solvent to achieve the separation , . The encapsulated ionic liquids (ENILs) have shown to impose no loss of the solvent absorbent capacity with a drastic enhancement of the CO 2 sorption rate, both for physical or chemical sorption driven solvents , , , …”
Section: Introductionmentioning
confidence: 99%
“…Brennecke and co-workers adopted the process of Stolaroff et al 118 to encapsulate basic ionic liquids ( Figure 28) and showed the microcapsules had an almost stoichiometric uptake of CO 2 above 0.4 bar, matching the free ionic liquid. 119 After CO 2 uptake and release, the capsules were broken open. 1 H NMR analysis of the ionic liquids did not show any degradation products.…”
Section: Water Remediationmentioning
confidence: 99%
“…The basic ionic liquids used by Brennecke and co-workers for entrapment in polymer microcapsules 119. …”
mentioning
confidence: 99%
“…Ionic liquids have emerged as a promising area in material science because of their tunable properties, allowing them to be used in a wide range of application such as: carbon dioxide capture, fuel cells, nanoparticle stabilization, and many more (Song et al, 2019;Huang et al, 2017;Wang et al, 2017). In this context, our group has been working on the synthesis of new cation moieties for ionic liquid designs.…”
Section: Structure Descriptionmentioning
confidence: 99%